2017
DOI: 10.1161/strokeaha.116.014950
|View full text |Cite
|
Sign up to set email alerts
|

Human Muse Cells Reconstruct Neuronal Circuitry in Subacute Lacunar Stroke Model

Abstract: Background and Purpose Muse cells are endogenous non-tumorigenic stem cells with pluripotency harvestable as pluripotent marker SSEA-3+ cells from the bone marrow (BM) from cultured BM-mesenchymal stem cells (MSCs). After transplantation into neurological disease models, Muse cells exert repair effects, but the exact mechanism remains inconclusive. Methods We conducted mechanism-based experiments by transplanting serum/xeno-free cultured-human BM-Muse cells into the peri-lesion brain at two weeks after lacun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
119
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(123 citation statements)
references
References 33 publications
3
119
1
Order By: Relevance
“…Therefore, Muse cells, in both the circulation and tissues, can selectively accumulate at the damaged site. After homing, Muse cells spontaneously differentiate into tissue-constituent cells and replenish damaged/lost cells to participate in tissue repair, as demonstrated following intravenous injection of exogenous Muse cells into animal models of stroke, encephalitis, acute myocardial infarction, renal failure, and liver damage 11 15 . Clinical data from patients with acute myocardial infarction and stroke indicate that the serum S1P levels increase prior to the increase in the number of endogenous PB-Muse cells after onset and this increase in the acute phase significantly correlates with functional recovery at 6 months, supporting a reparative function of Muse cells in vivo 11 , 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, Muse cells, in both the circulation and tissues, can selectively accumulate at the damaged site. After homing, Muse cells spontaneously differentiate into tissue-constituent cells and replenish damaged/lost cells to participate in tissue repair, as demonstrated following intravenous injection of exogenous Muse cells into animal models of stroke, encephalitis, acute myocardial infarction, renal failure, and liver damage 11 15 . Clinical data from patients with acute myocardial infarction and stroke indicate that the serum S1P levels increase prior to the increase in the number of endogenous PB-Muse cells after onset and this increase in the acute phase significantly correlates with functional recovery at 6 months, supporting a reparative function of Muse cells in vivo 11 , 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Muse cells were originally identified as cells that are resistant to long-term trypsin incubation and are known as cells that are double positive for the pluripotent surface marker, stage-specific embryonic antigen-3 (SSEA-3), and CD105, and that have the capacity for self-renewal and triploblastic differentiation from a single cell [6]. The applicability of Muse cells for regenerative treatments has been suggested in disease models of liver damage, stroke, skin ulcers related to diabetes mellitus, and osteochondral defects [9], [10], [11], [12].…”
Section: Introductionmentioning
confidence: 99%
“…But personally, the isolated Muse cells may change their characteristics under the severe culture stress. And two published studies are involved in magnetically activated cell sorting (MACS), but their isolation rate were only 77.1% and 71.3% [15,31].…”
Section: Distribution Of Muse Cells In the Bodymentioning
confidence: 99%
“…Mari Dezawa, the first to describe Muse cells, demonstrated that human Muse cells reconstructed neuronal circuity in subacute lacunar stroke SCID mice [15]. In the study, stroke was induced in SCID mice using the stroke model.…”
Section: Muse Cells Treated Strokementioning
confidence: 99%
See 1 more Smart Citation